The Plight of Women and Children: Advancing South Africa's Least Privileged. Issue 1 (March 2014) - Bower, Carol
Despite South Africa having ratified several international and regional women's and children's rights treaties, and having one of the most admired constitutions in the world, the plight of women and children after 20 years of democracy remains, in many respects, dire—especially in rural communities. South Africa is a deeply conservative and patriarchal society, with high levels of violence in general and gender-based violence in particular. It has failed to create sufficient employment opportunities and to sustainably address intergenerational poverty, the latter of which impacts most severely rural women and children. HIV/AIDS has wreaked its most adverse effects on women and children. This context is exacerbated by breakdowns in the health, education, justice, and security sectors; the relative inaccessibility of services (such as health care, schooling, and housing); and the frequently poor quality of services when they are available.